Charting the Exciton–Polariton Landscape of WSe2 Thin Flakes by Cathodoluminescence Spectroscopy. Issue 1 (25th November 2021) - Taleb, Masoud; Davoodi, Fatemeh; Diekmann, Florian K.; Rossnagel, Kai; Talebi, Nahid
Abstract : Semiconducting transition‐metal dichalcogenides (TMDCs) provide a fascinating discovery platform for strong light–matter interaction effects in the visible spectrum at ambient conditions. While most of the works have focused on hybridizing excitons with resonant photonic modes of external mirrors, cavities, or nanostructures, intriguingly, TMDC flakes of subwavelength thickness can themselves act as nanocavities. Herein, the optical response of such freestanding planar waveguides of WSe2 by means of cathodoluminescence spectroscopy is determined. Strong exciton–photon interaction effects that foster long‐range propagating exciton–polaritons and enable direct imaging of the energy transfer dynamics originating from cavity‐like Fabry–Pérot resonances are revealed. Furthermore, confinement effects due to discontinuities in the flakes are demonstrated as an efficient means to tailor mode energies, spin–momentum couplings, and the exciton–photon coupling strength, as well as to promote photon‐mediated exciton–exciton interactions. The combined experimental and theoretical results provide a deeper understanding of exciton–photon self‐hybridization in semiconducting TMDCs and may pave the way to optoelectronic nanocircuits exploiting exciton–photon interaction beyond the routinely employed two‐oscillator coupling effects. Abstract : Herein, room temperature exciton–polaritons (EPs) hosted by thin films of a semiconducting quantum material (WSe2 ) are explored using cathodoluminescence spectroscopy. The interference between the transition adiation (TR) and the EPs radiated from the edges of the flakes allow for probing the wavefront and propagation constant ( β EP ) of the EPs with high spatial resolution.